2022
DOI: 10.25165/j.ijabe.20221501.6888
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reducing and postponing controlled-release urea application on soil nitrogen regulation and maize grain yield

Abstract: Controlled-release urea (CRU-N) fertilizer application is a solution to improve the utilization rate of nitrogen (N), reduce economic costs and improve crop yields. It is significant to study the effects of release CRU-N reduction and the combined application of conventional urea on soil N control and the large-scale maize planting system. In this study, the effects of controlled-release nitrogen fertilizer reduction and postponement on soil nitrogen components, enzyme activities, and yields were investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…per ear and 100-grain weight, as it has been shown in previous stud-ies [4,19,38,42]. In this study, grain yield first increases and then decreases with an increase in the proportion of controlled-release nitrogen fertilization; this was likely because the increases in biomass accumulation and pre-anthesis dry matter remobilization were not accompanied by an increase in the proportion of controlled-release nitrogen fertilizer application, When the proportion of controlled-release nitrogen fertilizer application exceeds 70%, the accumulation of biomass showed a downward trend, which is in agreement with results from a previous study [41].…”
Section: Effect Of Controlled-release N Fertilization On Nitrogen Use...supporting
confidence: 91%
See 1 more Smart Citation
“…per ear and 100-grain weight, as it has been shown in previous stud-ies [4,19,38,42]. In this study, grain yield first increases and then decreases with an increase in the proportion of controlled-release nitrogen fertilization; this was likely because the increases in biomass accumulation and pre-anthesis dry matter remobilization were not accompanied by an increase in the proportion of controlled-release nitrogen fertilizer application, When the proportion of controlled-release nitrogen fertilizer application exceeds 70%, the accumulation of biomass showed a downward trend, which is in agreement with results from a previous study [41].…”
Section: Effect Of Controlled-release N Fertilization On Nitrogen Use...supporting
confidence: 91%
“…Soil enzyme activities were greatly increased under N fertilization, mainly because fertilizer application regulated the activities of enzymes involved in nutrient turnover's utilization of substrate [39,40]. At the silking stage, controlled-release nitrogen fertilization increased the associated enzymes involved in soil nitrogen utilization, such as soil urease, nitrate reductase, and nitrite reductase, to variable degrees, consistent with a previous study [41]. It is very important to improve the soil nitrogen supply and promote the nitrogen uptake of maize.…”
Section: Effect Of Controlled-release N Fertilization On Nitrogen Use...supporting
confidence: 89%
“…A large number of studies has shown that slow release or controlled release fertilizers, coated fertilizers and fertilizer synergists can significantly improve FUE. [40][41][42][43][44]. The methods of increasing the depth of fertilization have also been proved to be effective [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the activities of microbial biomass carbon and nitrogen in soil are signi cantly in uenced by urease activity and the amount of nitrogen fertilizer applied. Controlled-release nitrogen fertilizer enhances the activities of soil urease, protease, and nitrate reductase during the middle and late stages of crop growth [42][43] . Additionally, hydroxylamine reductase facilitates the conversion of soil hydroxylamine to nitrite, with its activity being augmented by nitrogen application [44] .…”
Section: The Impact Of Fertilization On Soil Properties and Crop Yieldmentioning
confidence: 99%